Representasi Perempuan dalam Film Sewu Dino - Pradipta, Karel Juan; Nurussa'adah, Erfina (Warta Ikatan Sarjana Komunikasi Indonesia, 2024)
Film is a mass communication medium that can display messages in audio and visual form simultaneously aimed at a particular group. As a form of mass media, films are also used to convey ideology to the general public. So quite a few women in films are positioned as inappropriate subjects. The film Sewu Dino is a horror film that features many female characters in it. This film is a film that still views women as negative subjects because the image of the majority of female characters is depicted as weak, oppressed both physically and psychologically. The aim of this research is to see how the image of women is depicted in the horror film Sewu Dino through the signs displayed. This research uses a qualitative approach using Roland Barthes' semiotic method. As a result of this research, the author explains the representation of women's images along with the signs or symbols in the film Sewu Dino. So that viewers of the film Sewu Dino or readers of this research can understand the meaning of the denotation, connotation and myth of the representation of the image of women depicted in the film Sewu Dino, which is depicted through their physical image such as long hair and brown skin color which is in accordance with Stuart's theory of representation. Hall is reflective. Then from the psychological image, women basically have a gentle nature, have a nurturing nature, and a high level of affection, which is in accordance with Stuart Hall's representation theory, namely intentional. As well as the depiction of the social image of women in which women are depicted as having a lower position than men and only carrying out the burdens given to them so that in the end they tend to be discriminated against, oppressed, and then make them become victims and are often depicted as ghosts in films which is in accordance with Stuart's representation theory. Hall is constructional.